CONTENT OF CREATIVE THINKING OF PRIMARY SCHOOL STUDENTS IN AN INNOVATIVE EDUCATIONAL ENVIRONMENT - Xhudoyberdiyeva A. X. (Galaxy International Interdisciplinary Research Journal, 2023)
This article reveals the analysis of cognitive universal educational actions in the educational process, the development of creative thinking of Primary School students and the content of its positive thinking in learning.